Generation 1.5 in college composition teaching academic writing to U.S.-educated learners of ESL - Roberge, Mark.; Siegal, Meryl.; Harklau, Linda. (Routledge, 2009)
Building on the work that has been done over the past decade, this volume provides theoretical frameworks for understanding debates about immigrant students, studies of students? schooling paths and language and literacy experiences, and pedagogical approaches for working with Generation 1.5 students.